Analisis Episode Kesalahan Membaca Nyaring di Sekolah Dasar - Darmiyati Zuchdi (Universitas Negeri Malang, 2016)
The purpose of this study was to analyze oral reading error episode in the elementary school, consisting of reading error, reaction of the reader, and feedback of the teacher. The subjects were teachers and students of the second and third grade of SDN Deresan 1 and SDN Ungaran 1, Yogyakarta. The data were collected by observing and recording oral reading activities. Descriptive statistical technique and loglinsar technique were employed to analyze data. It was found that the biggest number of oral reading error type was hesitancy. The biggest number of the sutdent's reaction toward their error was to stop for a moment, and the biggest number of interactions between class and oral reading error, class and students' reaction, school and teachers' feedback, and class and teachers' feedback